Living Condition, Economic and Stress Among Housewife During Covid-19 Pandemic - Samidah, Ida; Sofais, Danur Azissah Roesliana; Suyanto, Jipri (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Covid-19 is becoming a problem in many industries, particularly the economic sector. It may be related to a change in household income, which has prompted many issues in the household, such as baby nutrition, food security and safety, and so on. The problems caused by Covid -19 disease indicate a mother's discomfort and burden, which affects their mind and causes stress. This study aimed to investigate associated factors related to mothers’ stress in Bengkulu Province due to covid-19 pandemic term. A questionnaire was used as a research tool in the cross-sectional study. Mothers who had lived in Bengkulu Province for at least two years were the target respondents. The total number of respondents was 576, as determined by multistage random sampling. The respondents are residents of ten districts in Bengkulu Province. The questionnaire data were analyzed using logistic regression to identify variables associated with the mother's stress. The analysis showed that have associated with mothers’ stress included having a stunting baby, households that need a job, households with a low average of household income, living in urban, having bad living conditions, having a bad social influence, and low education. The covid-19 pandemic has been affected by changing economic situations that can change baby nutrition status because parents can't provide good nutrition, lose or reduce household income, need a good job, get bad living conditions, and have bad social influence among mothers in the Bengkulu Province area. Abstrak: Pandemik covid-19 menimbulkan permasalahan di berbagai sektor, terutama di bidang ekonomi. Perubahan ini menimbulkan penurunan pendapatan rumah tangga yang dapat menimbulkan banyak kesulitan tertentu di dalam rumah tangga, seperti kesulitan dalam memenuhi gizi, dan keutuhan primer lainnya. Permasalahan yang timbul menjadi indikator rasa ketidaknyaman dan beban pikiran kaum ibu yang berakhir dengan stress. Penelitian ini bertujuan untuk investigasi faktor atau indikator yang berhubungan dengan stress ibu di Provinsi Bengkulu dikarenakan kondisi pandemik covid-19. Penelitian ini menggunakan penelitian cross-sectional dengan menggunakan kuesioner online sebagai tool penelitian. Target responden dalam penelitian in adalah kaum ibu yang bertempat tinggal di Provinsi Bengkulu. Data yang diperoleh di analisa menggunakan Teknik regresi (bivariat dan multivariate) dalam melihat indikator yang paling mempengaruhi kejadian stress pada kaum ibu. Faktor yang berhubungan signifikan adalah anak yang memiliki kondisi stuning, keluarga yang membutuhkan pekerjaan, keluarga yang memiliki pendapatan rata-rata di bawah UMR, bertempat tinggal di kawasan perkotaan, kondisi hidup yang semakin tidak baik, pengaruh lingkungan yang tidak baik, dan Pendidikan yang rendah (SD dan SMP). Pandemik covid-19 memiliki pengaruhi besar terhadap perubahan ekonomi yang mempengaruhi pada status gizi anak, pekerjaan, pendapatan, kondisi hidup dan kehidupan sosial pada kaum ibu di kawasan Provinsi Bengkulu.